2020
DOI: 10.1177/0300060520932801
|View full text |Cite
|
Sign up to set email alerts
|

Association between EFHD2 gene polymorphisms and schizophrenia among the Han population in northern China

Abstract: Objective Schizophrenia is a severe neurodevelopmental disorder with a complex genetic and environmental etiology. The gene encoding EF-hand domain-containing protein D2 ( EFHD2) may be a genetic risk locus for schizophrenia. Methods We genotyped four EFHD2 single-nucleotide polymorphisms (281 schizophrenia cases [SCZ], 321 controls) from northern Chinese Han individuals using Sanger sequencing and polymerase chain reaction-restriction fragment length polymorphism analysis. Differences existed in genotype, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For SCZ, genetic factors from the family are one of the leading causes, implying at least one risk gene in this family (33,34). However, environmental factors also contribute to the onset of SCZ (35,36), and the environmental factors take effect because of the risk gene existence, such as Tmem108.…”
Section: Tmem108 Is One Of the Susceptible Genes In Sczmentioning
confidence: 99%
See 1 more Smart Citation
“…For SCZ, genetic factors from the family are one of the leading causes, implying at least one risk gene in this family (33,34). However, environmental factors also contribute to the onset of SCZ (35,36), and the environmental factors take effect because of the risk gene existence, such as Tmem108.…”
Section: Tmem108 Is One Of the Susceptible Genes In Sczmentioning
confidence: 99%
“…However, environmental factors also contribute to the onset of SCZ (35,36), and the environmental factors take effect because of the risk gene existence, such as Tmem108. The environmental factors may take part in the diseases through many routes, directly or indirectly interacting with the risk genes (33,34,37), and whether direct or indirect interaction between Tmem108 and SCZ is unclear.…”
Section: Tmem108 Is One Of the Susceptible Genes In Sczmentioning
confidence: 99%
“…It has been demonstrated that swiprosin-1 has a role in apoptosis, cell motility, spreading, migration, invasion, metastasis, actin-bundling or cross-linking, immune cell activation, brain cell functions, and so on [ 6 , 13 18 ]. Its expression is upregulated in many acute and chronic inflammatory diseases such as sepsis [ 19 ], passive cutaneous anaphylaxis and atopic dermatitis [ 9 ], Alzheimer’s disease [ 20 , 21 ], dementia [ 22 ], schizophrenia [ 16 , 23 ], diabetic nephropathy [ 24 , 25 ], and cancer [ 15 , 26 , 27 ], suggesting that swiprosin-1 played a role in inflammation processes of many diseases.…”
Section: Introductionmentioning
confidence: 99%